REBOUND: a media-based life skills and risk education programme - Jungaberle, Henrik; Nagy, Ede; Heyden, Maximilian von; DuBois, Fletcher (The Health education journal, 2015)
REBOUND is a novel media-based life skills and risk education programme developed for 14- to 25-year olds in school, university or youth group settings. This paper outlines the programme’s rationale, curriculum and implementation. It provides information of relevance to researchers, programme developers and policymakers.
Article first published online: November 16, 2014
Gesehen am 29.05.2020